On the Influence of Magnetic Field on Accretion Processes in CVs - D. V. Bisikalo; A. G. Zhilkin (Acta Polytechnica CTU Proceedings)
We consider the influence of such parameters as the value of the proper magnetic field Ba and the spin-rotation velocity of the white dwarf on accretion processes in CVs. The results of 3D MHD simulations have shown that the accretion rate is a non-monotonic function of Ba: with growing Ba it raises in the intermediate polars and decreases in the polars. The maximal accretion rate occurs in the systems, transiting from the stage of intermediate polars to polars; it’s value reaches 60% of the initially set mass transfer rate. We have also shown that the acretion rate decreases with the growing spin-rotation velocity of the white dwarf.